Pre-university Students' Voice Construction in Argumentative Essays. (August 2019) - Cheung, Yin Ling; Low, Tze Hui
This article examines how writer's voice is constructed in argumentative essays written at the pre-university level. The study focusses on the student writers' control over evaluative resources that influence the realization of voice in the high-scoring and low-scoring scripts. Using the APPRAISAL system in Systemic Functional Linguistics, the study shows how voice is construed through APPRAISAL theory in the high-scoring and low-scoring general paper essays, respectively. The differences between the two categories of essays can be seen in the application of ENGAGEMENT, ATTITUDE, and GRADUATION resources. Findings indicated that the high scoring essays used richer ENGAGEMENT and ATTITUDE resources to accomplish more mature and sophisticated argumentative voices. These opportunities to make full use of the APPRAISAL resources were missed by the low-scoring students in their argumentative writing. The findings are pedagogically useful for writing teachers who find the notion of voice too abstract to teach but accept its significance in producing a good essay.